Mixed convection flow about a solid sphere with constant heat flux embedded in a porous medium filled by a nanofluid: Buongiorno-Darcy model - Leony Tham; Roslinda Nazar; Ioan Pop (2014)
The laminar mixed convection boundary layer flow about a solid sphere in a nanofluid, which is maintained at a constant surface heat flux, has been studied via the nanofluid Buongiorno model and porous medium Darcy model for both cases of a heated and cooled sphere. The resulting system of nonlinear partial differential equations is solved numerically using an implicit finite-difference scheme known as the Keller box method. The solutions for the flow and heat transfer characteristics are evaluated numerically and studied for various values of the governing parameters, namely the Brownian motion parameter, thermophoresis parameter and mixed convection parameter. It is found that the boundary layer separates from the sphere for some negative values of the mixed convection parameter (opposing flow), and increasing the mixed convection parameter delays the boundary layer separation and the separation can be completely suppressed for sufficiently large values of the mixed convection parameter.